Supplementing energy and protein source at different rate of degradability to mixture of corn waste and coffee pod as basal diet on rumen fermentation kinetic of beef cattle - Pamungkas, Dicky; Utomo, R.; Ngadiyono, N.; Winugroho, M. (Indonesian Journal of Animal and Veterinary Sciences, 2010)
The use of corn waste and coffee pod as basal diet needs energy and protein supplementation in order to optimize rumen microbial growth. A research was done to study the appropriate supplement which is suitable based on the result of rumen fermentation kinetics. Four ruminally canulated cows, (205-224 kg of live weight) were placed in individual cages. The basal diet (BD) offered were corn waste and coffee pod mixture (80:20). Source of high degradable energy (HDE) was cassava pomace; while the low degradable energy (LDE) was arenga piñata waste. The high degradable protein (HDP) was mixed-concentrate while the low degradable protein (LDP) was leucaena leave meal. The supplementation of energy and protein to basal diet was in ratio of 50:50 based on dry matter. Feed offered were basal diet and the supplement at ratio of 60: 40 (3 % of LW). Observation was carried out for 4 periods (10 days/period). In each period, animal was fed one of the following diets:  A = BD, B = BD+ HDE+LDP, C = BD+LDE+LDP, and D = BD+HDE+HDP. Rumen kinetics observed were: pH, and VFA, NH3 and rumen microbial protein concentrations. Rumen fluid was taken at the end of each period gradually along the course of 24 hours fermentation. The results showed that the diets gave significant effect (P < 0.05) on rumen pH. The lowest rumen pH (5.76) was observed on diet D  at 2:00, 12 hours after feeding. Meanwhile, the highest pH (7.22) was found in animal fed diet A at 16:00. The total VFA on diet D of periode:1, 3 and 4 showed the highest level: 68.1 mmol/l; 75.37 mmol/l and 85.14 mmol/l respectively. The highest NH3 concentration was found in diet D followed  by diet C, B and A. At 12:00 observation or at 4 h after morning feeding the highest NH3 was observed from diet D (41.94 mg/100 ml). It is concluded that diet D resulted in the best rumen fermentation kinetic, therefore it could be used in feed formulation in cattle diets. Key words: Corn Waste, Coffee Pod, Degradation, Rumen Fermentation